The Power of Anti-Corruption Education in Shaping Social Attitudes: A Mediation Perspective - Widodo Widodo; Jossapat Hendra Prijanto; Rahayu Permana; Juniriang Zendrato; Triyani Ambar Sari (Yayasan Keluarga Guru Mandiri, 2026)
Corruption cases continue to occur, potentially eroding social attitudes, including those of students. Therefore, this study aims to explore the influence of anti-corruption education on social attitudes through perceptions of corruption. The research uses a quantitative approach, survey methods, and a causal design. The population comprises 880 private junior high school students in Bekasi Regency, West Java, while the sample consists of 275 students. Sampling was conducted using a random proportional sampling method at each school. Data collection was conducted using a Likert-scale questionnaire, and analysis was conducted using the Structural Equation Modeling approach based on Partial Least Squares (SEM-PLS). The results show that anti-corruption education negatively affects perceptions of corruption and positively impacts students' social attitudes. Perceptions of corruption negatively affect students' social attitudes and mediate the influence of anti-corruption education on those attitudes. These findings yield new empirical evidence of the mediating role of perceptions of corruption in the causal relationship between anti-corruption education and students' social attitudes. This model makes theoretical contributions to psychology and educational management, particularly in shaping social attitudes through anti-corruption education. Furthermore, it can be used to optimize anti-corruption education as a strategy to prevent corruption and foster positive social attitudes among students.